2022
DOI: 10.3389/fmicb.2022.1012516
|View full text |Cite
|
Sign up to set email alerts
|

Allicin shows antifungal efficacy against Cryptococcus neoformans by blocking the fungal cell membrane

Abstract: Allicin, which is generated by the catalytic reaction between alliin and alliinase extracted from garlic, has been shown to have a wide range of antimicrobial activities, but its anti-Cryptococcus efficacy and mechanism are not quite clear. Here, we have determined that the Conversion rate of allicin in the reaction product reached 97.5%. The minimal inhibitory concentration (MIC) of allicin against Cryptococcus neoformans (C. neoformans) H99 was 2 μg/ml, which is comparable to fluconazole (FLU, 1 μg/ml). Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Ogita et al found that in Saccharomyces cerevisiae , allicin enhanced fungicidal activity of AmB by inhibiting ergosterol trafficking from the plasma membrane to the vacuole membrane ( 32 ). Li et al recently reported that allicin exerted antifungal efficacy against Cryptococcus neoformans by regulating plasma membrane-related pathways to block the cell membrane ( 33 ). The effects of allicin on fungal cell membrane were also reported by Khodavandi et al, Aala et al, and Kim et al ( 27 , 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ogita et al found that in Saccharomyces cerevisiae , allicin enhanced fungicidal activity of AmB by inhibiting ergosterol trafficking from the plasma membrane to the vacuole membrane ( 32 ). Li et al recently reported that allicin exerted antifungal efficacy against Cryptococcus neoformans by regulating plasma membrane-related pathways to block the cell membrane ( 33 ). The effects of allicin on fungal cell membrane were also reported by Khodavandi et al, Aala et al, and Kim et al ( 27 , 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The antifungal sensitivity tests were repeated twice, and any tests with abnormal results were repeated three times. Candida parapsilosis ATCC22019 and Candida krusei ATCC6258 were used as quality controls according to the CLSI M27 guidelines ( CLSI, 2017 ; Tóth et al, 2019 ; Li et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, even for amphotericin B-insensitive bacteria, allicin showed good antifungal activity against 46 clinical isolates of C. neoformans, with MICs ranging from 1 to 8 µg/mL. It is worth mentioning that allicin also had additive or synergistic effects when mixed with FLU and amphotericin B [176]. Aside from the basic interaction mechanism of allicin with the -SH groups of cellular proteins, some studies have indicated that allicin impacts specific target enzymes such as acetyl-CoA synthetase [177].…”
Section: Exploration Of Allium Metabolites For Antimicrobial Activitymentioning
confidence: 99%